Seasonal records of palaeoenvironmental change and resource use from archaeological assemblages. (October 2018) - Prendergast, Amy L.; Pryor, Alexander J.E.; Reade, Hazel; Stevens, Rhiannon E.
Abstract: Seasonal climate variability can affect the availability of food, water, shelter and raw materials. Therefore, robust assessments of relationships between environmental change and changes in human behaviour require an understanding of climate and environment at a seasonal scale. In recent years, many advances have been made in obtaining seasonally-resolved and seasonally-focused palaeoenvironmental data from proxy records. If these proxy records are obtained from archaeological sites, they offer a unique opportunity to reconstruct local climate variations that can be spatially and temporally related to human activity. Furthermore, the analysis of various floral and faunal remains within archaeological sites enables reconstruction of seasonal resource use and subsistence patterns. This paper provides an overview of the growing body of research on seasonal palaeoenvironmental records and resource use from archaeological contexts as well as providing an introduction to a special issue on the same topic. This special issue of Journal of Archaeological Science Reports brings together some of the latest research on generating seasonal-resolution and seasonally-focused palaeoenvironmental records from archaeological sites as a means to assessing human-environment interaction. The papers presented here include studies on archaeological mollusc shells, otoliths, bones and plant remains using geochemical proxies including stable isotopes (δ 18 O, δ 13 C, δ 15 N) and trace elements (Mg/Ca). The geographical scope encompasses parts of Europe, North America and the Levant, while temporally the studies range from Palaeolithic to historical times.